2016
DOI: 10.4103/0377-4929.188103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of phenotypic and genotypic detection of methicillin resistance among Staphylococcus aureus

Abstract: Results of oxacillin screen agar and cefoxitin DD test were in concordance with mecA gene PCR. Thus, it is determined that especially cefoxitin test can be an alternative to PCR in routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…Aynı şekilde çalışmalarında fenotipik ve genotipik yöntem arasında iyi bir korelasyon bulan çalışmalar bulunmaktadır. 16,17 Birçok çalışma, özellikle bakteri ve ilgi genlerin tespit için PCR'ın uygun olduğunu 18 , stafi lokokal antibiyotik direnç genlerinin tespitinde PCR'ın uygulanabilirliğini göstermiştir. 19 Ayrıca önceki çalışmalar mecA geninin doğru saptanmasında PCR'ın önemini kanıtlamıştır.…”
Section: Discussionunclassified
“…Aynı şekilde çalışmalarında fenotipik ve genotipik yöntem arasında iyi bir korelasyon bulan çalışmalar bulunmaktadır. 16,17 Birçok çalışma, özellikle bakteri ve ilgi genlerin tespit için PCR'ın uygun olduğunu 18 , stafi lokokal antibiyotik direnç genlerinin tespitinde PCR'ın uygulanabilirliğini göstermiştir. 19 Ayrıca önceki çalışmalar mecA geninin doğru saptanmasında PCR'ın önemini kanıtlamıştır.…”
Section: Discussionunclassified
“…It has been suggested that the efficacy of the cefoxitin test is superior to that of the oxacillin test and that it sometimes can be used as an alternative to PCR. 39 The phenotypic methods of MRSA identification are time-consuming and have their limitations in terms of generating false-positive and falsenegative results leading to delay or ineffective antibiotic prescriptions; however, they are still commonly used because of the unavailability and high cost of PCR materials and few experienced staff to carry out PCR techniques.…”
Section: Dovepressmentioning
confidence: 99%
“…As much as 25% of HA-SA patient’s isolates were resistant to cefoxitin. Resistance to cefoxitin encoded by mecA gene, set up in specific location of chromosome, and can be transmitted from bacteria to other bacterial species (Demir et al, 2016). Infection by MRSA was a major problem for health systems worldwide.…”
Section: Discussionmentioning
confidence: 99%